Characteristics of Social Studies Lesson Study in Mikawa Area, Aichi Prefecture, Japan: The Case of 6th Grade â€œI want to know more about the nearest country, Korea!â€ - Shirai, Katsuhisa (The Indonesian Journal of Social Studies, 2018)
The purpose of this research is to clarify the characteristics of social studies lesson study in the Mikawa area of Aichi Prefecture in Japan and to show comparative viewpoints on social studies lesson study in Indonesia. For that purpose, I took up the practice of â€œI want to know more about Â the nearest country: Korea!â€ Through the examination of this practice, I identified the following three points as what we achieve through social studies lesson study: (1)Â we are creating a conceptual diagram of the social studies unit; (2)Â we are preparing a teaching instruction plan; and (3)Â we are conceiving a temporary arrangement and a method of practice. In this study, I examine the significance and the problem.